In the face of war: examining sexual vulnerabilities of Acholi adolescent girls living in displacement camps in conflict-affected Northern Uganda - Patel Sheetal H; Muyinda Herbert; Sewankambo Nelson K; Oyat Geoffrey; Atim Stella; Spittal Patricia M (BMC, 2012)
Abstract Background Adolescent girls are an overlooked group within conflict-affected populations and their sexual health needs are often neglected. Girls are disproportionately at risk of HIV and other STIs in times of conflict, however the lack of recognition of their unique sexual health needs has resulted in a dearth of distinctive HIV protection and prevention responses. Departing from the recognition of a paucity of literature on the distinct vulnerabilities of girls in time of conflict, this study sought to deepen the knowledge base on this issue by qualitatively exploring the sexual vulnerabilities of adolescent girls surviving abduction and displacement in Northern Uganda. Methods Over a ten-month period between 2004-2005, at the height of the Lord's Resistance Army insurgency in Northern Uganda, 116 in-depth interviews and 16 focus group discussions were held with adolescent girls and adult women living in three displacement camps in Gulu district, Northern Uganda. The data was transcribed and key themes and common issues were identified. Once all data was coded the ethnographic software programme ATLAS was used to compare and contrast themes and categories generated in the in-depth interviews and focus group discussions. Results Our results demonstrated the erosion of traditional Acholi mentoring and belief systems that had previously served to protect adolescent girls' sexuality. This disintegration combined with: the collapse of livelihoods; being left in camps unsupervised and idle during the day; commuting within camp perimeters at night away from the family hut to sleep in more central locations due to privacy and insecurity issues, and; inadequate access to appropriate sexual health information and services, all contribute to adolescent girls' heightened sexual vulnerability and subsequent enhanced risk for HIV/AIDS in times of conflict. Conclusions Conflict prevention planners, resettlement programme developers, and policy-makers need to recognize adolescent girls affected by armed conflict as having distinctive needs, which require distinctive responses. More adaptive and sustainable gender-sensitive reproductive health strategies and HIV prevention initiatives for displaced adolescent girls in conflict settings must be developed.